2011
DOI: 10.1175/2010mwr3338.1
|View full text |Cite
|
Sign up to set email alerts
|

A Space–Time Multiscale Analysis System: A Sequential Variational Analysis Approach

Abstract: As new observation systems are developed and deployed, new and presumably more precise information is becoming available for weather forecasting and climate monitoring. To take advantage of these new observations, it is desirable to have schemes to accurately retrieve the information before statistical analyses are performed so that statistical computation can be more effectively used where it is needed most. The authors propose a sequential variational approach that possesses advantages of both a standard sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 23 publications
1
73
0
Order By: Relevance
“…In this case, as explained for the one-dimensional case in Section 2.2, the error variance reduction produced by each observation can be considered as an additional reduction to the reduction produced by its neighboring observations. This additional reduction is smaller than the reduction produced by a single observation, so the error variance reduction produced by analyzing the coarse-resolution observations is bounded above by ∑ Δ 2 (x), which is similar to that for the onedimensional case in (4). For the same reason as explained for the one-dimensional case in (4), this implies that the domain-averaged value of ∑ Δ 2 (x) is larger than the true averaged reduction estimated by Δ 2 ≡ 2 − 2 , where 2 is the domain-averaged analysis error variance estimated by the spectral formulation for two-dimensional cases in Section 2.3 of Xu et al [8].…”
Section: Uniform Coarse-resolution Observations With Periodicmentioning
confidence: 62%
See 2 more Smart Citations
“…In this case, as explained for the one-dimensional case in Section 2.2, the error variance reduction produced by each observation can be considered as an additional reduction to the reduction produced by its neighboring observations. This additional reduction is smaller than the reduction produced by a single observation, so the error variance reduction produced by analyzing the coarse-resolution observations is bounded above by ∑ Δ 2 (x), which is similar to that for the onedimensional case in (4). For the same reason as explained for the one-dimensional case in (4), this implies that the domain-averaged value of ∑ Δ 2 (x) is larger than the true averaged reduction estimated by Δ 2 ≡ 2 − 2 , where 2 is the domain-averaged analysis error variance estimated by the spectral formulation for two-dimensional cases in Section 2.3 of Xu et al [8].…”
Section: Uniform Coarse-resolution Observations With Periodicmentioning
confidence: 62%
“…The equality in (4) is for the limiting case of Δ co / → ∞ only. The inequality in (4) implies that the domainaveraged value of ∑ Δ 2 ( ) is larger than the true averaged reduction estimated by Δ 2 ≡ 2 − 2 , where 2 is the domain-averaged analysis error variance estimated by the spectral formulation for one-dimensional cases in Section 2.2 of Xu et al [8].…”
Section: Uniform Coarse-resolution Observations With Periodicmentioning
confidence: 99%
See 1 more Smart Citation
“…Through fusing multi-source data from ground measurements, satellite observations and numerical model products, the CLDAS provides high-quality gridded hourly Ta, air pressure, humidity, wind speed, precipitation and surface shortwave radiation. The fusion of temperature, air pressure, humidity and wind speed is mainly achieved by the Space-Time Multiscale Analysis System (STMAS), which is an upgraded version of Local Analysis and Prediction System (LAPS) of the National Oceanic and Atmospheric Administration (NOAA) [50,51] using the multi-grid sequential variational method. Validation study of this product showed the bias and root mean square error (RMSE) of Ta are less than 1 K and 1.5 K, respectively, benchmarked with national automatic ground station observed air temperature in China [52].…”
Section: Modis Lst Productmentioning
confidence: 99%
“…When data assimilation is applied to a fine-resolution model, small-scale structures are subjected to strong filtering effects [Daley, 1991]. A few studies have demonstrated that a set of data assimilation should be applied for a sequence of reduced decorrelation length scales [e.g., Xie et al, 2011;Zhang et al, 2011]. In the MS-DA algorithm, the cost function is decomposed for distinct spatial scales.…”
Section: Introductionmentioning
confidence: 99%